India and the united states in a changing world - Kapur, Ashok (ed.); Malik, Y. K. (ed.); Gould, Harold A. (ed.) (New Delhi, 2002)
This important and timely volume not only explores the many strands and nuances of the chequered course of Indo-US relations, but offers pragmatic policy recommendations. The original essays by reputed scholars and analysts cover a wide range of fundamental issues affecting bilateral relations. The contributors maintain that the rapidly growing rapprochement between India and the United States could have far-reaching implications for peace and progress throughout Asia.
Keywords: Political Science